Sistema de controle para turbina eólica de eixo vertical - Ramos, André Jaques (2018)
This master thesis presents the development of a control system to vertical axis wind turbine in order to harnessing its maximum performance. Vertical axis turbine designs and how they could be integrated with urban area are studied, together with a review in literature about methods that aim to improve its coefficient of power and start up condition under very low winds. The turbine in test can generate 1.5 kW employing a permanent magnet synchronous machine. In order to extract the maximum performance is used a DC-DC converter in combination with maximum power point tracking algorithm. The converter supplies a resistive load for experimental tests. Due to the rotor be unreachable, there was no way to measure rotor speed, so that, one current sliding mode observer and an adaptive electromotive force observer are combined resulting in rotor speed estimation. Besides, modelling and simulation aspects about rotor velocities and forces using blade element momentum method are presented to understand its behaviour and how they affect the turbine performance. This analysis is compared with manufacturer data and experimental results.